Hubungan Efikasi Diri Terhadap Prestasi Belajar IPS Siswa Sekolah Dasar - Makmur Nurdin; Rahmawati Patta (Seminar Nasional LP2M UNM, 2019)
The main problem that is considered in this study, is the quality of education is not determined by a single factor, namely student learning outcomes which are a reflection of learning effort, the better the learning effort, the better the results achieved. Good learning outcomes will be achieved if they can overcome the learning difficulties they experience, but there are a number of variables that influence each other. This type of research is ex-post facto causality. The population in this study were elementary students of Mitra PGSD Bone. Data were collected through 54 selected samples using cluster random sampling techniques. This study aims to: (1) To find a picture of self-efficacy, (2) To find out and explain the relationship of self-efficacy to students' social studies learning achievement. Data were analyzed with descriptive statistics and inferential statistical analysis. The results showed that: (1) Most elementary students had: self-efficacy in the medium category, and social studies learning outcomes in the moderate category; (2) Self-efficacy has a significant relationship with students' social studies learning achievement. Conclusions, if students' self-efficacy continues to be improved will have an impact on learning outcomes that are even better and can make adjustments in the learning process.